HUBUNGAN PENGETAHUAN BEACH SAFETY DENGAN TINDAKAN KESELAMATAN PADA WISATAWAN DI PANTAI KUTA BALI - Gusti Ayu Made Sri Sunari; Ni Luh Putu Eva Yanti; Kadek Cahya Utami (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Kuta beach is one of the tourist place in the province of Bali that is often visited by tourists for swimming and surfing, but this activity often causes accidents for tourists. The aims of this study to determine the correlation between beach safety knowledge with the safety action of tourists in Kuta Beach. This type of research is cross-sectional. The research sample of 96 tourists who had swum and surfed in Kuta Beach and were selected using consecutive sampling techniques. Data collection of beach safety knowledge and safety action using a questionnaire. The bivariate analysis used the Gamma test with a confidence level of 95% (? = 0.05). Statistical test results show that there is a significant correlation between beach safety knowledge with the safety action of tourists with a significance value of 0,000 (p-value<0.05). Respondents’ generally lack of knowledge of noticing the warning signs and beach flags. The safety action among respondents were on the medium level as it may be caused by their knowledge, motivation, attitude, values and belief were not strong enough to drive their beach safety act. The Lawrence Green theory also supports that knowledge and action are correlated. Researcher recommend that life guard can provide adequate education about beach safety to every visitors using posters or any other learning media, for those who are willing to do beach activities including surfing and swimming needs to make further notice to life guard.